2016
DOI: 10.7717/peerj.2603
|View full text |Cite
|
Sign up to set email alerts
|

Bone protein “extractomics”: comparing the efficiency of bone protein extractions ofGallus gallusin tandem mass spectrometry, with an eye towards paleoproteomics

Abstract: Proteomic studies of bone require specialized extraction protocols to demineralize and solubilize proteins from within the bone matrix. Although various protocols exist for bone protein recovery, little is known about how discrete steps in each protocol affect the subset of the bone proteome recovered by mass spectrometry (MS) analyses. Characterizing these different “extractomes” will provide critical data for development of novel and more efficient protein extraction methodologies for fossils. Here, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 56 publications
3
54
0
Order By: Relevance
“…A number of protocols have been reported for the extraction of ancient proteins, particularly for the extraction of bone protein [81][82][83] , and include protocols based on SDS buffers and polyacrylamide gels ( 24,84 ), Filter-Aided Sample Preparation (FASP) 1,85,86 , and Gel-Aided Sample Preparation (GASP) 87,88 . However, the efficacy of these protocols, their downstream effect on protein identification and resulting chemically-induced modification have not been systematically compared in studies of ancient proteins, although examples exist that compare their performance on modern material 89,90 .…”
Section: Laboratory Considerationsmentioning
confidence: 99%
“…A number of protocols have been reported for the extraction of ancient proteins, particularly for the extraction of bone protein [81][82][83] , and include protocols based on SDS buffers and polyacrylamide gels ( 24,84 ), Filter-Aided Sample Preparation (FASP) 1,85,86 , and Gel-Aided Sample Preparation (GASP) 87,88 . However, the efficacy of these protocols, their downstream effect on protein identification and resulting chemically-induced modification have not been systematically compared in studies of ancient proteins, although examples exist that compare their performance on modern material 89,90 .…”
Section: Laboratory Considerationsmentioning
confidence: 99%
“…Although the ‘NaOH’ fraction possessed a greater number of collagen I PSMs than the NaOH-400/200/4 fraction (table 1), the number of unique peptides and per cent sequence coverage for all proteins were either substantially greater in the NaOH-400/200/4 fraction, or roughly equal between the two (electronic supplementary material, table S2). This suggests that unlike demineralization treatments [15], the NaOH pretreatment is not extracting a different subset of proteomic information than the following solubilization step. Further, the nearly identical results obtained from the pretreated (NaOH-400/200/4) and non-treated (400/200/4) fractions (table 1 and electronic supplementary material, table S2) indicate that NaOH pretreatment under these conditions does not improve the capacity of the 400/200/4 to solubilize proteins from the bone matrix.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 143 protein groups (71.5%) were detected in both the EDTA and the pellet fractions, and 154 protein groups (77.0%) were retrieved from both rib and vertebra. Recovered proteomes can differ in multiple experimental fractions extracted from a single sample 32 and from different bone elements from a single individual 33 . PANTHER analysis indicated that 51.6% of protein groups are classified as an extracellular component (Supplementary Table 3) and 41.3% are related with binding function (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%